β2-Agonist Induced cAMP Is Decreased in Asthmatic Airway Smooth Muscle Due to Increased PDE4D - Trian, Thomas; Burgess, Janette K.; Niimi, Kyoko; Moir, Lyn M.; Ge, Qi; Berger, Patrick; Liggett, Stephen B.; Black, Judith L.; Oliver, Brian G. (PloS one, 2011)
Asthma is associated with airway narrowing in response to bronchoconstricting stimuli and increased airway smooth muscle (ASM) mass. In addition, some studies have suggested impaired β-agonist induced ASM relaxation in asthmatics, but the mechanism is not known. To characterize the potential defect in β-agonist induced cAMP in ASM derived from asthmatic in comparison to non-asthmatic subjects and to investigate its mechanism. We examined β(2)-adrenergic (β(2)AR) receptor expression and basal β-agonist and forskolin (direct activator of adenylyl cyclase) stimulated cAMP production in asthmatic cultured ASM (n = 15) and non-asthmatic ASM (n = 22). Based on these results, PDE activity, PDE4D expression and cell proliferation were determined. In the presence of IBMX, a pan PDE inhibitor, asthmatic ASM had ∼50% lower cAMP production in response to isoproterenol, albuterol, formoterol, and forskolin compared to non-asthmatic ASM. However when PDE4 was specifically inhibited, cAMP production by the agonists and forskolin was normalized in asthmatic ASM. We then measured the amount and activity of PDE4, and found ∼2-fold greater expression and activity in asthmatic ASM compared to non-asthmatic ASM. Furthermore, inhibition of PDE4 reduced asthmatic ASM proliferation but not that of non-asthmatic ASM. Decreased β-agonist induced cAMP in ASM from asthmatics results from enhanced degradation due to increased PDE4D expression. Clinical manifestations of this dysregulation would be suboptimal β-agonist-mediated bronchodilation and possibly reduced control over increasing ASM mass. These phenotypes appear to be "hard-wired" into ASM from asthmatics, as they do not require an inflammatory environment in culture to be observed.